Facebook as an Agent to Tackle Climate Change with Reference to University Students in Assam (Indian Journal of Social Science and Literature (IJSSL), 2024)
The world is living in crucial times of climate change with an adverse impact on our planet. It is therefore vital for everyone to understand the implications of being ignorant of the causes of climate change. The need for increasing awareness is greater now than ever before, and the best means available for this is through extensive use of social media. The proliferation of social media tools in this information age is tremendous. The effect of popular social media platforms like Facebook and its patterns of usage by university students need to be investigated. The global outreach of various platforms of digital media is unparalleled. Social media could be a desirable platform to fight against all the odds in climate change. This study investigates the usage patterns of Facebook as an agent to tackle climate change amongst the university students in Assam. The study is exploratory in nature and executed through a quantitative research methodology. The data is collected by employing survey method with close ended questionnaire as its research tool. This study analyses the opinions drawn from 100 university students studying in various universities in Assam. The data has been taken through snowball sampling technique and measured with Likert Scale. It is pertinent to understand the level of awareness of the university going students about climate change. Perhaps, this is high time to analyse the usage patterns of Facebook by university students and spell out the rationale behind its effectiveness in fighting against climate change.